PERANAN SIA SEBAGAI ALAT BANTU MANAJEMEN TERHADAP PENGAMBILAN KEPUTUSAN DALAM PENENTUAN HARGA JUAL PADA UMKM ‘TOKO DESI’ - Yaohan Ad’nnia Jannah; Hwihanus Hwihanus (Pusat Riset dan Inovasi Nasional, 2023)
Information systems in modern times now have a fairly important role in the progress of an organization, including in the business world. The obstacles that often arise in Small and Medium Enterprises (SME) namely on a transaction system that is still manual, with using paper to archive company data. Thus it will clearly make it difficult to control financial report data and transaction data. For this reason, it is important to earn for a certain system which able to help process transaction data and reports, which can also be useful for interested parties to overcome these obstacles. The required application system is an Accounting Information System. This research was conducted using quantitative analysis methods, namely by collecting accurate data. The aim of this research is none other than to analyze the effect of management information systems on decision making at Desi stores. The data collection method used by researchers is to create a questionnaire. The sample studied was 20 respondents using simple linear regression data analysis techniques. The influence of information systems in making decisions on selling prices at Desi Store is 67.4%. As the result of this research we can see that accounting information system for ‘Desi stores’ has played an effective and efficient role as a management tool in making pricing decisions, because most of the selling prices in 'Desi stores' use prices suggested by the official salesperson of these products. However, data processing and recording of company financial reports at 'Desi stores' still use a fairly simple method, namely with using paper to archive company data.